PERSONIFICATION IN GELONG MARO AS ORAL LITERATURE TANA TORAJA COMMUNITY - Anastasia Baan (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
Gelong Maro is a poem that is one of the oral literature of the Tana Toraja community. Gelong Maro has two unique aspects, namely in terms of pronunciation or delivery. Gelong Maro is delivered in a more upbeat and rhythmic rhythm so that the speaker can interpret or feel the presence of the Gods when singing maro poetry. Furthermore, the uniqueness of the spiritual aspect is Gelong Maro which contains expressions, prayers, and hopes that are very meaningful. Where the dancers chant maro poetry that aims to refuse reinforcements and can be a means of healing for the dancer or people who experience disease. The highlight of Gelong Maro is possession. The purpose of this presentation is to describe the meaning of personification in Gelong Maro as the oral literature of the Tana Toraja community. To understand the extent of personification, a qualitative study was conducted. The data source for the study came from the Gelong Maro video recording spoken by Tominaa Ne'Lumba. The techniques used in collecting data are listening and interview techniques. The results showed that the meaning of personification in Gelong Maro is containing disclosures that attach human traits to inanimate objects and abstract ideas and include the joints of Toraja people's lives.